Living Beyond Norms: A Qualitative Study on Public Perception and Lived Realities of Unmarried Middle-Aged Women in Medan - Annisa Umamy; Muhammad Habibi Siregar (Journal of General Education and Humanities, 2025)
Marriage is often considered an important phase in the lives of Indonesian women, reflecting the success and completeness of a woman's identity as a wife and mother. However, an increasing number of middle-aged women (aged 40–60) are unmarried in an ever-evolving social context. This phenomenon elicits diverse responses from society, ranging from negative stigma to social pressure, which ultimately affects the comfort and psychological well-being of women who experience it. This study aims to explore middle-aged women's perceptions of marriage, identify factors hindering marriage, and understand their conditions and expectations as unmarried women. The study uses a descriptive qualitative approach with in-depth interviews with four main informants and four supporting informants in Medan. Data were analyzed through thematic reduction and categorization. The study results show that middle-aged women perceive marriage as a form of worship and a long-term commitment. Although they had a desire to marry in the past, they experienced various obstacles, including emotional trauma, the absence of a serious partner, and social and cultural pressure. Nevertheless, they demonstrated economic and emotional independence and were able to build a positive meaning of life outside the institution of marriage. Family support proved to be an important factor in maintaining psychological stability. This study concludes that the single status of middle-aged women results from a complex life process, not merely a form of failure. Therefore, society needs to stop stigmatizing and build a more inclusive understanding of women's life choices.